2021
DOI: 10.1007/s00127-020-02005-5
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial interventions for self-harm in low-income and middle-income countries: systematic review and theory of change

Abstract: Purpose-To synthesise the evidence on effectiveness, acceptability and the delivery mechanisms of psychosocial interventions for self-harm in low and middle income countries and to develop a pathway of change specific for self-harm interventions.Method-Studies reporting one or more patient or implementation outcomes of a psychosocial intervention targeting self-harm and conducted in low-and middle-income countries were included. Taxonomy of treatment components and a theory of change map was created using info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…Adolescents who self-harm often have poor emotion regulation and social problem-solving skills. 4 One systematic review 5 suggested that these deficits could be addressed by adapting cognitive behaviour and problem solving therapies. Treatments that have been developed or adapted to the local service system context, including service providers' knowledge and experience and young service users' lived experiences, are likely to be most effective and scalable.…”
Section: Black Men Wanted For Restraint and Research?mentioning
confidence: 99%
See 2 more Smart Citations
“…Adolescents who self-harm often have poor emotion regulation and social problem-solving skills. 4 One systematic review 5 suggested that these deficits could be addressed by adapting cognitive behaviour and problem solving therapies. Treatments that have been developed or adapted to the local service system context, including service providers' knowledge and experience and young service users' lived experiences, are likely to be most effective and scalable.…”
Section: Black Men Wanted For Restraint and Research?mentioning
confidence: 99%
“…They need to use the inhumanity of these experiences to advocate for better resources and accountability to victims and their families. 5 We call for a coalition, on the basis of humanitarian principles, to insist that we value, respect, and dignify the bodies of all service users: particularly Black men who are disproportionately represented within the mental health system. We must replace coercive practice with compassion and community engagement.…”
Section: Black Men Wanted For Restraint and Research?mentioning
confidence: 99%
See 1 more Smart Citation
“…Known effective interventions to prevent these problems exist but have not yet been well implemented in Nigeria. [31][32][33][34][35] We have provided comprehensive estimates for the burden of diseases in Nigeria, filling a gap in evidence that has severely curtailed the ability of policy makers to improve the health of Nigerians. Through standardised methods we have been able to investigate patterns of health loss between time periods and across comparable nations of west Africa.…”
Section: Discussionmentioning
confidence: 99%
“…4 For effective systemic responses, robust data surveillance, predictive modelling, and multisectoral coordination are required. 5 We declare no competing interests. Data in parentheses are percentage increase compared with the previous year.…”
Section: Suicide Prevention Strategy In Indiamentioning
confidence: 99%